2021
DOI: 10.3389/fcvm.2021.737285
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Vascular Cell Adhesion Molecule-1 (sVCAM-1) Is Associated With Left Atrial Remodeling in Long-Distance Runners

Abstract: Introduction: An increased risk of atrial fibrillation (AF) has been demonstrated in high-performance athletes. Soluble vascular adhesion molecule-1 (sVCAM-1), a biomarker involved in inflammation and cardiac remodeling, is associated with the development of AF in the general population. However, the relationship between sVCAM-1 and left atrial (LA) remodeling has been poorly investigated in long-distance runners (LDR).Aim: To determine the association between LA remodeling and sVCAM-1 levels in LDR during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…An Italian study showed that endurance athletes had significantly larger dimensions of the left atrium (LA) and LV but did not have significantly thicker LV walls. In addition, previous studies showed that, compared with team sports, endurance sports present an increased risk of AF after controlling for accumulated hours of activity [ 8 , 14 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], as shown in Fig. 3 .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…An Italian study showed that endurance athletes had significantly larger dimensions of the left atrium (LA) and LV but did not have significantly thicker LV walls. In addition, previous studies showed that, compared with team sports, endurance sports present an increased risk of AF after controlling for accumulated hours of activity [ 8 , 14 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], as shown in Fig. 3 .…”
Section: Resultsmentioning
confidence: 97%
“…Thus, sVCAM-1 is a possible biomarker for evaluating and monitoring potential negative effects, including AF, on LA structure and function in high-performance athletes because sVCAM-1 level is positively linked to the increased LA volume, as shown in Fig. 4 [ 37 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“… 43 Soluble vascular cell adhesion molecule-1 (sVCAM-1) is a protein that plays a key role in fibrosis and cardiac remodeling 44 and migration of leukocytes to the vessels, 45 and it may act in endothelial dysfunction. 46 Serum levels of sVCAM-1 were higher than healthy control regarding COVID-19 patients. 47 Increased inflammation, platelet dysfunction, and imbalances in the coagulation mechanism in COVID-19 infection have caused disruptions in the normal coagulation mechanism.…”
Section: Introductionmentioning
confidence: 84%
“…IL-10 is an anti-inflammatory cytokine that is produced by Th2 cells and monocytes, known to be elevated in AD, and functions to decrease Th1 associated cytokine expression 33 , 34 . Finally, there were also increased levels of general inflammatory molecules in PN plasma, such as sVCAM-1 and sICAM-1 which are known to facilitate leukocyte adhesion and migration across the blood vessel endothelium 35 , 36 , as well as the acute phase reactant SAA, which promotes inflammation by activating the inflammasome cascade, inducing synthesis of pro-inflammatory cytokines, and acting as a chemotactic for neutrophils and mast cells 37 . Each of these general inflammatory markers are known biomarkers of cardiovascular disease, which disproportionately affects patients with PN 3 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%